Security Loans in Recent Years - Roelse, Harold V. (The Review of Economics and Statistics, 1930)
A FREQUENT tendency in interpreting the available figures as to security loans has been to follow one series and to base conclusions on that series with little regard other data that are available. A year ago, much attention was given to the mounting totals of brokers' loans, and very little to the figures on the total security loans of weekly reporting member banks. Recently the tendency has been to direct attention chiefly to the fact that the total security loans of the reporting banks are close to the highest levels ever reported. No single series is sufficiently comprehensive to give an adequate view of the situation. All of the more important series loans to brokers and dealers in securities reported by the principal New York City banks, the borrowings of Stock Exchaange members, and the total security loans of all weekly reporting member banks overlap to a considerable degree, yet each of them contains elements that are not included in the others. Consequently, in order to obtain an idea of the total amount of security loans, or of changes in the total, it is necessary to combine the various series, using part of each. The following table presents such a combination of the available figures June 30, 1930, together with the corresponding figures a year previous, and October 4, 1929, when approximately the highest level of security loans was reached. For these dates it was possible to use the figures on security loans of all member banks which have been compiled recently by the Federal Reserve Board. By deducting the loans of reporting member banks on approximately the same dates from the loans of all member banks, it was possible to obtain close estimates of the amount of security loans of member banks that do not report weekly, and these estimates are shown in the table. In view of the fact that the data weekly reporting banks include loans to banks on securities whereas the data all member banks do not, it was necessary to make a small estimated adjustment such loans. The loans to New York City brokers non-member banks and other out-of-town lenders were obtained by deducting the street loans of member banks outside New York City from brokers' loans placed for account of out-of-town banks. Undoubtedly this latter item, which is included in the weekly brokers' loan reports, included last year a considerable amount placed, not the out-of-town banks' own account, but their customers. The figures in the table have been rounded off, and some adjustments have been made differences in dates between the weekly member banks reports and the condition (all member banks) reports. This compilation leaves unaccounted the loans of non-member banks to brokers and dealers in securities outside of New York City, and to the other customers of these banks. It may be estimated that, as these non-member banks include only a small proportion of the large banks in leading cities and a considerable proportion of country banks, their total security loans may have amounted to between 2 and 3 billion dollars during the past two years. The indicated totals of all reported security loans show that, notwithstanding the fact that the security loans of weekly reporting banks have been higher recently than ever before, except two weeks at the time of the stock market break last autumn, the total volume of security loans at the end of June was about 412 billion dollars less than at the high point of last autumn, and about 3 billion dollars less than in June of last year. All of the decrease has been in brokers' loans placed lenders other than member banks; in fact, withdrawals of funds by such lenders have exceeded the large reduction in the total amount of brokers' loans. The recent high level of security loans in the reporting banks is due chiefly to their replacing with their own funds a part of the brokers' loans withdrawn by other lenders at the time of the break in the stock market last autumn and during the subsequent decline in call loan rates to unattractive levels. The security loans of the weekly reporting member banks now constitute at least two-thirds of reported security loans, whereas last autumn they represented less than one-half of the total.